Study of stump-liner/socket interface movement for ICEROSS Seal-in X5 and Dermo Liners in transtibial amputees / Hossein Gholizadeh Vazvani - Hossein, Gholizadeh Vazvani (2012)
The method of attachment of prosthesis to the residual limb (suspension) and socket fitting is a critical issue in the process of providing an amputee with prosthesis. Different suspension methods try to minimize the pistoning movement inside the socket to enhance the amputee’s gait and satisfaction. The ICEROSS Seal-In® X5 and Dermo® Liner by Ossur are new suspension liners that intend to reduce pistoning between the socket and liner. Since the effects of these new liners on suspension during ambulation are unclear, this study aimed to evaluate the pistoning effect of these liners on ten transtibial amputees. To achieve the aim of the study, two prostheses with ICEROSS Seal-In® X5 and the ICEROSS Dermo® Liner were fabricated for each subject by the researcher himself. The vertical displacement within the socket in static positions and during the gait (dynamic) was measured using two novel methods (Vicon motion system and a photographic method) for the first time in this study. The reproducibility of measurements in different trials of one session and between two sessions by two observers was shown to be high. These new methods enabled the researcher to measure the pistoning between the liner and prosthetic socket. The results demonstrated that the pistoning within the socket when ICEROSS Seal-In® X5 was used decreased (71%) in comparison to the ICEROSS Dermo® Liner. Furthermore, a significant difference between the two liners under different static and dynamic conditions was found (p<0.05). Participants needed to put in extra effort for donning and doffing the prosthesis with ICEROSS Seal-In® X5 liner; however, this type of liner provided less pistoning during the ambulation. These new approaches that use the motion analysis system or photographic method in this study can be an alternative for measuring the pistoning effect in the prosthetic socket.